Evaluating the ecotoxicity of polymer-coated SPIONs for scale inhibition using a zebrafish embryo model - Farah M. El-Makaty (22475386) (2026)
Superparamagnetic iron oxide nanoparticles (SPIONs) are increasingly explored as sustainable scale inhibitors in oilfield operations, offering high efficiency, magnetic recoverability, and reduced chemical discharge. This study evaluates the environmental safety of two polymer-coated SPION formulations—SPIONs-TSC-PPEA and SPIONs-TSC-PASP—through a comprehensive zebrafish embryo model, aligned with OECD guidelines. The nanocomposites demonstrated complete inhibition of gypsum and calcite scaling at ≤10 ppm, while maintaining high survival (>90%), hatching, and minimal teratogenicity in zebrafish embryos up to 200 ppm—representing a 20× safety margin. Mechanistic assessments of cardiac and neuromotor functions revealed only mild, adaptive effects. Physicochemical characterization confirmed stable, monodispersed nanoparticles with low dissolution and high surface charge. These findings confirm the low ecotoxicological risk of SPION-based inhibitors, supporting their integration into environmentally responsible scale management strategies. This study advances sustainable nanotechnology solutions by bridging performance, recyclability, and environmental compliance. Other Information Published in: Colloids and Surfaces B: Biointerfaces License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://doi.org/10.1016/j.colsurfb.2025.115215